PENGARUH PENGETAHUAN PAJAK DAN SANKSI PAJAK TERHADAP NIAT UNTUK PATUH CALON WAJIB PAJAK - Dewi Kusuma Wardani; Fidia Nur Rahmadini (Bajang Institute, 2022)
This study aims to test whether tax knowledge and tac sanctions affect the intention to comply with prospective taxpayers. This study uses a quantitative description method and primary data using a questionnaire. The number of samples in this study were 100 student respondents from the Universitas Sarjanawiyata Tamansiswa Yogyakarta in the class of 2018, 2019 and 2020. Sampling in this research uses snowball sampling technique. This research gives the result that tax knowledge has no effect on tax compliance intentions and tax sanctions have no effect on tax compliance intentions.